Prospecting fractured rock aquifers using radon soil gases method - Stefano, Paulo Henrique Prado (2017)
Groundwater prospecting  in fractured aquifers depends on the detection of tectonic lineaments, which may be difficult in urban areas.  A survey was carried out using radon soil gases concentrations in four localities in the region of Granite Santana and Viamão Granite, Porto Alegre, Rio Grande do Sul, in order to test the method for water prospecting in fractured aquifers. The radon data have been compared with electrical resistivity survey executed using dipole-dipole arrangement. At four studied areas, an interesting correlation was noted between the two methods. At regions of low resistivity, positive radon anomalies were found in fracture zones, reaching values up to 7 times the background of the region, starting from a concentration value of 2500 Bq/m3 in a non-fractured zones to 22187 Bq /m3 in the fractured zones.